Recent agricultural policy developments and options in Romania - Clapan C.; Stoforos C.; Mergos G. (Selected readings on economies in transition, 2000)
The drive towards trade liberalisation as evidenced by the recent conclusions of the GATT Uruguay Round has forced governments to focus on the effects of trade protection and distortions. Agricultural price policy has especially been recognised as a crucial area in which government intervention has introduced major distortions. Clarifying the impact of agricultural policy on the whole agro-chain provides policy makers with better feedback on the impact of their decisions, which is particularly important in the Central and Eastern European countries (CEECs). This paper aims to analyse the different changes in agricultural policy and trade that have occurred since 1989 in Romania and their impacts on agricultural developments in the process of the integration into the European economy. It also shows the use of a partial equilibrium multi-product model for the Romanian agriculture for the simulation of alternative policy choices.